1999
DOI: 10.1016/s0006-3495(99)77108-0
|View full text |Cite
|
Sign up to set email alerts
|

Two Groups Control Light-Induced Schiff Base Deprotonation and the Proton Affinity of Asp85 in the Arg82His Mutant of Bacteriorhodopsin

Abstract: Arg(82) is one of the four buried charged residues in the retinal binding pocket of bacteriorhodopsin (bR). Previous studies show that Arg(82) controls the pK(a)s of Asp(85) and the proton release group and is essential for fast light-induced proton release. To further investigate the role of Arg(82) in light-induced proton pumping, we replaced Arg(82) with histidine and studied the resulting pigment and its photochemical properties. The main pK(a) of the purple-to-blue transition (pK(a) of Asp(85)) is unusual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 73 publications
3
25
0
Order By: Relevance
“…Mutated protein substituting R82 with Gln, Ala or Lys delays the proton release from the EC until after proton uptake via D96 . In the R82H mutant, the t‐O to t‐bR transition is slowed, indicating that R82 is important for the proton transfer from the CC to the EC. The analysis here will focus on the wild‐type protein where the large, positively charged R82 appears to be a major component in the region between the CC and the EC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutated protein substituting R82 with Gln, Ala or Lys delays the proton release from the EC until after proton uptake via D96 . In the R82H mutant, the t‐O to t‐bR transition is slowed, indicating that R82 is important for the proton transfer from the CC to the EC. The analysis here will focus on the wild‐type protein where the large, positively charged R82 appears to be a major component in the region between the CC and the EC.…”
Section: Resultsmentioning
confidence: 99%
“…This process is likely to be slowed by generating a high‐energy neutral Arg if following a proton‐hopping pathway, or because a lower‐energy but longer Grotthuss‐type pathway is rarely formed. Since R82 does not actively participate in a Grotthuss‐type pathway, this may help explain how the R82 mutant proteins can still pump protons …”
Section: Resultsmentioning
confidence: 99%
“…53 It is worthwhile to note that this cooperativity disappears also when Arg82 is replaced with lysine or histidine. 54 Since the side-chain of this residue is shown to undergo a pronounced structural change during the purpleto-blue transition ( Figure 5), it is very likely that Arg82 plays an important role in mediating a strong coupling between the proton release complex and Asp85, as has been suggested by the structural analysis of the M intermediate. [10][11][12][13] The diffraction data from alkalized crystals show that the proton release complex undergoes a different type of structural change at around pH 10.…”
Section: Crystal Structures Of Bacteriorhodopsinmentioning
confidence: 85%
“…22 The much slower proton transfer from Asp85 to the PRG in the O-to-bR transition of Arg82His as compared to the wild-type further supports an important functional role of Arg82. 23 Multiconformation equilibrium electrostatics computations suggested that Arg82, when oriented towards the Schiff base region, stabilises the zwitterionic state with protonated Schiff base and negatively-charged Asp85. In contrast when oriented towards the PRG, Arg82 stabilises the unprotonated Schiff base/protonated Asp85 (M-like) state, and the deprotonated state of the PRG.…”
Section: Introductionmentioning
confidence: 99%